Educating Students to Improve the World - Reimers, Fernando M. (SpringerBriefs in Education, 2020)
This open access book addresses how to help students find purpose in a rapidly changing world. In a probing and visionary analysis of the field of global education Fernando Reimers explains how to lead the transformation of schools and school systems in order to more effectively prepare students to address today's' most urgent challenges and to invent a better future. Offering a comprehensive and multidimensional framework for designing and implementing a global education program that combines cultural, psychological, professional, institutional and political perspectives the book integrates an extensive body of empirical literature on the practice of global education. It discusses several global citizenship curricula that have been adopted by schools and school networks, and ties them into an approach to lead school change into the uncharted territory of the future. Given its scope, the book will help teachers, school and district leaders tackle the change management needed in order to introduce global education, and more generally increase the relevancy of education. In addition, the book offers a "bridge" for more productive collaboration and communication between those who lead the process of educational change, and those who study and theorize this important work. At a time when the urgency of our shared global challenges calls for more understanding and collaboration and when the rapid transformation of societies requires that we help students develop a clear sense of relevancy and purpose, this book offers a way to pursue deep and sustainable change in instruction and school culture, so that students learn that nothing human is foreign and that they can find meaning in lives aligned with audacious purposes to make the world better.